Bell Pepper Biowaste Products as Medicinally Valuable Nutraceuticals: A Comprehensive Review - Areej Hazem Alyamoor; Yasser Fakri Mustafa (University of Mosul, 2023)
Background: The numerous additional valued substances present within plant biowaste products have a wide range of candidates regarding their recycling, promoting the idea of the circular economy. The bell pepper (BP, Capsicum annum L.) has high concentrations of various vitamins and minerals. Also, the biowastes of this plant, including the peels, seeds, and leaves, can represent valuable starting factors for creating medicinal chemicals as an alternative for increasing outcomes and waste in BP production and utilization in the food industrial fields. Aim: This article evaluates the necessary information about the chemical compositions of various colored BP fruits and their associated biomedical characteristics. The BP seeds, fruits, or leaves are rich in bioactive substances such as phenols, flavonoids, carotenoids, α-tocopherol, and pectic polysaccharides. These bioactive molecules may have the ability to be utilized as nutritional substances and display antioxidant, antifungal, antimicrobial, immune-suppressive, and immune-stimulant characteristics. Revalorization of food biowaste products appears in this way as a highly technological and unique field of study with beneficial effects on consumers, finance, and the health of the planet. Conclusion: To make sure that the use of these molecules is effective and to understand their principles of action, more study is required.